Amphipoda from Jørgen Brønlund Fjord, North Greenland. - Just, Jean (Meddelelser om Grønland, 1970)
From Jørgen Brønlund Fjord, North Greenland 28 species of Amphipods are listed, one of which is new to science, viz. Byblis arcticus. Four known species and one Genus are new to Greenland waters. Notes on breeding biology are made where possible and maps of distribution of Monoculodes schneideri G. 0. SARS and Aceroides l. latipes G. 0. SARS are presented. Anatomical and morphological problems of Corophium clarencense SHOEMAKER are mentioned briefly.